The mediatized nostalgic narrative: the case of the 2018 presidential election - Carlotto, Thiago Haas (Anais de Artigos do Seminário Internacional de Pesquisas em Midiatização e Processos Sociais, 2021)
We seek to reflect on how the campaign of candidates Jair Bolsonaro (PSL), aligned to the right of the political spectrum, as well as Fernando Haddad, from the Workers' Party (PT), aligned to the left, made use of narratives that refer to idealized memories, to assert their identity and prospect voters. This work presents a bibliographical research about nostalgia, from its perception as a psychological illness in the 17th century, its application in the media during modernity, to the emergence of retrotopia, that is, the utopia of the past, in post-modernity. Then, it brings a review of mediatization, its relationship with human evolution, its environment and its articulation with the perception of time and, by extension, with nostalgia.